Systems of assessment for the selection of sewers by selected garment producers - Mijares, Charles Raymund Jose A.; Arribas, Lydia B. (1999.)
The garments industry is a competitive manufacturing industry, which goals are to provide the right products at the right time in the right quantity and price. One way to become competitive is to have skilled and very qualified workers to provide necessary knowledge, skills and abilities to produce a product. The research aimed to identify a standard which was used by the garments industry to select its sewers. This was found important by the researcher from the fact that the sewers were the ones who manipulated the flat fabric into a three-dimensional product. It was a qualitative study that focused on the management point-of-view regarding the selection process. The research found that the common method of selection was the performance test. This was a practical skills test that sampled the knowledge, skills and abilities of sewers. The performance test was used to identify the operative skill of a sewer, the technical know-how in construction of a garment, and the extent of the sewers' abilities to interpret designs and the cut fabric construction in the assembly of a garment. The researcher concluded that the performance test used in the industry today identified sufficient information about the sewers' knowledge, skills and abilities for the purpose of companies. The challenge remains in the development of a standard rating procedure for the accurate assessment of the sewers knowledge, skills and abilities.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing workers -- Evaluation